2008
DOI: 10.1002/anie.200705154
|View full text |Cite
|
Sign up to set email alerts
|

From an N‐Methyl N‐Heterocyclic Carbene to Carbyne and Carbide Ligands via Multiple CH and CN Bond Activations

Abstract: Multiple choices: The carbyne C atom of 1 and the carbide of 2 arise from an N‐methyl group of 1,3‐dimethylimidazol‐2‐ylidene. The synthesis of complex 1, which involves activation of the three CH bonds of an N‐methyl group, and that of complex 2, which requires additional activation of the CN bond, provide new examples of metal‐mediated degradation of N‐heterocyclic carbenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 46 publications
1
46
0
Order By: Relevance
“…28 The X-ray structure of 23 ( Fig. 5) 28 shows that this hexanuclear complex arises from the condensation of two molecules of 19 and that it contains a quadruply-bridging carbyne fragment that arises from the activation of the third C-H bond of the original N-Me group. This structure is related to those of [Ru 6 (m 3 -H) 2 (m 5 -k 2 -ampy)(m-CO) 2 (CO) 14 ] (H 2 ampy = 2-amino-6-methylpyridine), which contains a quadruplybridging nitrene ligand, 29 and [Ru 6 (m 3 -H)(m 5 -k 2 -MebipyC)-(m-CO) 3 (CO) 13 ] (Me 2 bipy = 6,6 0 -dimethyl-2,2 0 -bipyridine), which contains a chelating Mebipy attached to a quadruplybridging carbyne fragment.…”
Section: Ruthenium Andmentioning
confidence: 99%
See 1 more Smart Citation
“…28 The X-ray structure of 23 ( Fig. 5) 28 shows that this hexanuclear complex arises from the condensation of two molecules of 19 and that it contains a quadruply-bridging carbyne fragment that arises from the activation of the third C-H bond of the original N-Me group. This structure is related to those of [Ru 6 (m 3 -H) 2 (m 5 -k 2 -ampy)(m-CO) 2 (CO) 14 ] (H 2 ampy = 2-amino-6-methylpyridine), which contains a quadruplybridging nitrene ligand, 29 and [Ru 6 (m 3 -H)(m 5 -k 2 -MebipyC)-(m-CO) 3 (CO) 13 ] (Me 2 bipy = 6,6 0 -dimethyl-2,2 0 -bipyridine), which contains a chelating Mebipy attached to a quadruplybridging carbyne fragment.…”
Section: Ruthenium Andmentioning
confidence: 99%
“…28 The NHC ligands of 45 and 47 arise from the cleavage of one C-N (45) or three C-H bonds (47) of the original Mes 2 Im ligand of compound 39. Using a 13 CO-enriched sample of compound 39, it has been determined that this carbide ligand arises from a thermallyinduced cleavage of CO, as had been previously observed for other carbide derivatives of osmium carbonyl.…”
Section: Ruthenium Andmentioning
confidence: 99%
“…La 4 Al 8 clusters and one La 5 Al 9 cluster produced multiple C À H bond activation featuring methylene, methine, or carbide C 1 functionalities. [16,17] The observation of methane and Me 3 AlA C H T U N G T R E N N U N G (PMe 3 ) in the NMR spectra, the irreversibility of the reaction, and the elemental analyses (Table 1) indicate that the few isolated crystals studied by X-ray diffraction must be similar in composition to the major product of the reaction.…”
Section: Reactivity Of [Lna C H T U N G T R E N N U N G (Alme 4 ) 3 ]mentioning
confidence: 99%
“…2 However, since the first study of the reaction of Ru 3 (CO) 12 with tetraaminealkenes (IEt 2 H 2 ) 2 to give complex Ru 3 (CO) 11 (IEt 2 H 2 ) reported by Lappert and Pye in 1977, 3 only a few reports dealing with Ru 3 (CO) 12 and NHCs ligands have been published. [4][5][6][7][8][9][10][11] Among these reactions, some abnormal intramolecular C-X (X = H, N) bond cleavage was observed. Cabeza et al demonstrated the synthesis of [Ru 3 (CO) 11 (Me 2 Im)] (Me 2 Im=1,3dimethylimidazol-2-ylidene) and its transformation into [Ru 3 (m-H) 2 (MeImCH)(CO) 9 ] through a process involving unusual reversible cleavage of two C-H bonds of a N-methyl group.…”
Section: Introductionmentioning
confidence: 99%